Fast Gating for Raman Spectroscopy - Andrea Chiuri; Federico Angelini (Sensors, 2021)
Fast gating in Raman spectroscopy is used to reject the fluorescence contribution from the sample and/or the substrate. Several techniques have been set up in the last few decades aiming either to enhance the Raman signal (CARS, SERS or Resonant Raman scattering) or to cancel out the fluorescence contribution (SERDS), and a number of reviews have already been published on these sub-topics. However, for many reasons it is sometimes necessary to reject fluorescence in traditional Raman spectroscopy, and in the last few decades a variety of papers dealt with this issue, which is still challenging due to the time scales at stake (down to picoseconds). Fast gating (<1 ns) in the time domain allows one to cut off part of the fluorescence signal and retrieve the best Raman signal, depending on the fluorescence lifetime of the sample and laser pulse duration. In particular, three different techniques have been developed to accomplish this task: optical Kerr cells, intensified Charge Coupling Devices and systems based on Single Photon Avalanche Photodiodes. The utility of time domain fast gating will be discussed, and In this work, the utility of time domain fast gating is discussed, as well as the performances of the mentioned techniques as reported in literature.